Reading prosocial content in books and adolescents’ prosocial behavior: A moderated mediation model with evidence from China - Li, Wu; Zhou, Liuning; Ai, Pengya; Kim, Ga Ryeung (Frontiers in Psychology, 2022)
Drawing upon the General Learning Model, the present study developed a moderated mediation model to provide an in-depth understanding of whether and how adolescents' reading prosocial content in books predicts their prosocial behavior. A paper-based survey was adopted to collect data from Chinese participants to test the proposed hypotheses. The results showed that prosocial content reading was positively associated with adolescents' prosocial behavior directly and indirectly through the mediation of moral identity. Furthermore, this study revealed the moderation effect of age on the relationships among prosocial content reading, moral identity, and prosocial behavior. Specifically, as age increases, the effects of prosocial content reading on moral identity and prosocial behavior attenuate, and the mediation effect of moral identity also decreases. The study adds to the body of knowledge on the prosocial media effect by extending it to book reading.